2014
DOI: 10.1002/cssc.201403182
|View full text |Cite
|
Sign up to set email alerts
|

Singlet‐Oxygen Oxidation of 5‐Hydroxymethylfurfural in Continuous Flow

Abstract: Singlet-oxygen oxidation of 5-hydroxymethylfurfural (5-HMF) was performed in continuous flow mode using rose Bengal as photosensitizer. The resulting butenolide (H(2) MF) was formed selectively in high yield. The procedure proved to be scalable and applicable to related bio-based furfurals. Furthermore, preliminary data show that H(2) MF can be readily isomerized thermally to 5-hydroxy-4-keto-pentenoic acid oligomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 26 publications
(18 reference statements)
0
50
0
Order By: Relevance
“…199 However, Kappe et al recently developed a continuous-flow procedure for the H 2 MF production to form 5-HMF. 200 The microreactor was built from commercially available PFA tubing (1 mm ID, 10 mL) and wrapped around a glass cylinder. As a light source, a 60 W compact fluorescent light bulb was employed.…”
Section: Homogeneous Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…199 However, Kappe et al recently developed a continuous-flow procedure for the H 2 MF production to form 5-HMF. 200 The microreactor was built from commercially available PFA tubing (1 mm ID, 10 mL) and wrapped around a glass cylinder. As a light source, a 60 W compact fluorescent light bulb was employed.…”
Section: Homogeneous Catalysismentioning
confidence: 99%
“…Singlet oxygen oxidation of 5-HMF in continuous flow. 200 Heterogeneous catalysis. Immobilization of photosensitizers for the production of singlet oxygen in microreactors can beneficial for several reasons (e.g., catalyst recuperation, high TON, easy work-up procedures).…”
Section: Homogeneous Catalysismentioning
confidence: 99%
“…A possible way to circumvent this in microreactors might be by the addition of an inert carrier phase in which the precipitated FDCA particles are dispersed, preventing them from interacting with the microreactor wall or solid catalysts. [292][293][294][295] Oxygenated monoterpenes are promising building blocks for the synthesis of pharmaceuticals, flavorants and fragrances. Some research has been done recently on the oxidation of HMF to FDCA using ionic liquids in which FDCA dissolves well, [287,288] however, the application of ionic liquids for industrial production is not economically feasible yet.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Prompted by these encouraging results, a multitude of reactor designs -including microfluidic chip reactors [150], falling-film reactors [151], dual-and triplechannel microreactors [152,153], coil-based devices [154,155], gas-permeable micro-capillary films [156], and tube-in-tube membrane devices [157] -were subsequently applied for the generation and subsequent utilization of 1 O 2 in gas/liquid continuous flow regimes using well-known photosensitizers such as Rose Bengal, methylene blue, and porphyrins. Furthermore, it was shown that porphyrins can be immobilized on the channel wall of a glass microreactor to heterogeneously catalyze the formation of the reactive oxygen species [158].…”
Section: Oxidative Carbon-carbon Coupling Reactionsmentioning
confidence: 99%